A Five-Year strategic financial plan for Grand Plaza Hotel Corporation - Balboa, Justin Daniel T., Esteves, Rolyn Mae C., Montalan, Mary Lexine S., Murata, Akimae Rose R., Peralta, Clarissa Aubrey D., San Buenaventura Alih T., Tarriela, Jessica Mae M. 4 0 16; 5
Executive Summary: The Grand Plaza Hotel Corporation is facing financial difficulties marked by declining liquidity, increasing reliance on debt, and inconsistent profitability. Although the company benefits from a strong brand and presence in the hospitality industry, it operates within a highly competitive and concentrated market dominated by larger players with greater resources. The financial analysis highlights significant issues in liquidity and efficiency, underscoring the need for enhanced cash management and optimized operations to maintain financial stability. To address these challenges, this paper offers several strategic recommendations aimed at bolstering the company's financial position, including debt restructuring, equity financing, operational efficiencies, and market expansion initiatives. Key factors impacting Grand Plaza's financial health include a downward trend in liquidity ratios, heightened dependency on debt financing, and fluctuations in profit margins. This analysis suggests that improved cash management and enhanced asset utilization are critical to increasing the company's financial resilience and ability to meet its short-term obligations. Specifically, improving the current liquidity position would provide stronger operational stability, while reducing reliance on debt financing could alleviate financial risk and lessen interest expenses. Furthermore, enhancing operational efficiency through cost control, workforce optimization, and refined service offerings would likely improve profit margins, positioning the company to better respond to market shifts. In addition, Grand Plaza could explore growth opportunities by extending its reach to underserved market segments and bolstering its brand presence. By engaging with these customer groups and expanding across various channels, such as digital marketing and strategic partnerships, the company has the potential to achieve sustained revenue growth and strengthen its competitive foothold in the market. This paper delivers a detailed financial analysis of Grand Plaza's recent performance, examining liquidity, profitability, solvency, and operational efficiency. Findings point to critical areas of improvement and actionable steps to support the company's goals of achieving financial stability and growth. By implementing these strategies, Grand Plaza Hotel Corporation aims to improve profitability and ensure long-term sustainability in a competitive and evolving hospitality landscape. Through strategic adjustments, Grand Plaza can enhance its market positioning, secure greater financial resilience, and sustain its presence as a key player in the hospitality industry
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2